Islamic Microfinance – an Inclusive Approach with Special Reference to Poverty Eradication in Pakistan - Khaleequzzaman, Muhammad; Shirazib, Nasim Shah (International Journal of Economics, Management and Accounting, 2013)
The paper attempts to highlight some issues of conventional microfinance leading to irrational results and suggests alternative mechanism of Islamic microfinance to alleviate poverty in more effective manner. The results of the research are based on extensive review of literature comparing both the systems and finding reasonable ground for Islamic microfinance to be more inclusive and viable. Owing to time constraint, data set of Pakistan Poverty Alleviation Fund was used to assess impact of conventional microfinance which suggested that change in poverty status of the poorest was not significant, rather the affluent poor benefitted the most. While making a case for Islamic microfinance, the paper suggests extending its scope through product diversification, innovation and downscaling operations of Islamic banks linking microfinance institutions, particularly for fund sourcing, Sharia’ advisory, and technology transfer. The question of inclusion therefore needs to be addressed through Islamic poverty alleviation process, building assets of the target segments which could bring socio-economic change in their lives. An outline of a few Islamic products has been recommended in view of specific features of microenterprises and risk management. JEL Classification: G21, P46, P51 Keywords: Microfinance, Islamic Microfinance, Product development, Paki-stan